2016
DOI: 10.1097/md.0000000000005677
|View full text |Cite
|
Sign up to set email alerts
|

Sputum pentraxin 3 as a candidate to assess airway inflammation and remodeling in childhood asthma

Abstract: Pentraxin 3 (PTX3) is a soluble pattern recognition receptor and an acute-phase protein. It has gained attention as a new biomarker reflecting tissue inflammation and damage in a variety of diseases. Aim of this study is to investigate the role of PTX3 in childhood asthma.In total, 260 children (140 patients with asthma and 120 controls) were enrolled. PTX3 levels were measured in sputum supernatants using enzyme-linked immunosorbent assay test. We performed spirometry and methacholine challenge tests and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…The effect of the CdCl 2 treatment on fi lm texture was previously reviewed in detail by Kim et al, [ 26 ] who took θ -2 θ scans during the annealing stage as the temperature was gradually ramped from room temperature to 500 °C. This study revealed two key stages of the recrystallization process: First, an increase in the {111} peak from 300 to 375 °C (stage 1), and then a rapid Table 1.…”
Section: Microstructural Properties Of Treated Cdte Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the CdCl 2 treatment on fi lm texture was previously reviewed in detail by Kim et al, [ 26 ] who took θ -2 θ scans during the annealing stage as the temperature was gradually ramped from room temperature to 500 °C. This study revealed two key stages of the recrystallization process: First, an increase in the {111} peak from 300 to 375 °C (stage 1), and then a rapid Table 1.…”
Section: Microstructural Properties Of Treated Cdte Devicesmentioning
confidence: 99%
“…[ 27 ] Elsewhere, Kim et al [ 26 ] interpreted the evolution of XRD peaks for different sets of planes as a function of temperature as being a result of Adv. [ 27 ] Elsewhere, Kim et al [ 26 ] interpreted the evolution of XRD peaks for different sets of planes as a function of temperature as being a result of Adv.…”
Section: Microstructural Properties Of Treated Cdte Devicesmentioning
confidence: 99%
“…Circulating CRP levels were also shown to be significantly elevated in steroid‐naïve patients with asthma compared with healthy controls and steroid‐treated asthma patients and increased in non‐allergic, but not allergic, asthma . Meanwhile, enhanced expressions of PTX3 were also observed in asthmatic biopsy samples and in sputum of children with asthma . However, evidence to date has not explicitly linked pentraxin levels to airway inflammation phenotype in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Serum high sensitivity‐CRP levels, which may be a useful predictor of airway inflammation, have been shown to be significantly higher in asthma patients compared to healthy controls . Elevated PTX3 expression in asthmatic airways has also been observed, and sputum PTX3 levels, a candidate biomarker for evaluation of airway inflammation and remodelling, were also shown to be increased in children with asthma . However, currently, very little is known about expression of SAP in asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation